1983
DOI: 10.1079/bjn19830071
|View full text |Cite
|
Sign up to set email alerts
|

Iron absorption from a malted cocoa drink fortified with ferric orthophosphate using the stable isotope58Fe as an extrinsic label

Abstract: 1. The potential use of an extrinsic label to measure iron absorption from a ferric orthophosphate-fortified malted cocoa drink was examined by measuring the solubility of the FePO4 in 0·1 M-hydrochloric acid.2. The validity of using the stable isotope 58Fe as an extrinsic label was tested by comparing Fe absorption by rats from wheat flour extrinsically-labelled with 58Fe or 59Fe.3. Fe absorption from a malted cocoa drink (20 g powder made up with hot water) fortified with FePO4 (0·5 mg Fe/g powder) was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…In addition. thc lc\cl ol' bovine 1 .I' in the stoolc 01' I I -(la!-oltl infi~nts k d 1.1-li)stilicd o r ~~nfi)rtificd li)r-mulac W:IS nicasurctl to disco\el-to n h a t extent the l.f'w;rs br-oLcn tlowli I>y tligcsti\c eri/!,rncs :inti micr-oorganisrns.…”
mentioning
confidence: 99%
“…In addition. thc lc\cl ol' bovine 1 .I' in the stoolc 01' I I -(la!-oltl infi~nts k d 1.1-li)stilicd o r ~~nfi)rtificd li)r-mulac W:IS nicasurctl to disco\el-to n h a t extent the l.f'w;rs br-oLcn tlowli I>y tligcsti\c eri/!,rncs :inti micr-oorganisrns.…”
mentioning
confidence: 99%
“…While the high mineral content of cocoa and chocolate is not disputed, the extent to which the minerals are available to the body has provoked discussion and research. Studies have shown that the body efficiently utilises most minerals present in cocoa (Fairweather‐Tait et al 1983; Brown et al 1990).…”
Section: Nutrient Composition Of Cocoa and Chocolatementioning
confidence: 99%
“…The iron available from soya protein (a vegetable) is high and compares well with that from meat products (Layrisse et al, 1969;Sayers, Lynch & Jacobs, 1973). However, this has been contradicted in some studies (Ashworth & March, 1973;Bjorn-Rasmussen et al, 1973). The role of soya protein in iron nutrition has become of particular interest recently when a series of studies demonstrated inhibitory effects on iron absorption of soya products in semisynthetic meals.…”
Section: Availability Of Iron From Common Foodsmentioning
confidence: 99%